Effect of Land Application of Phosphorus-Saturated Gypsum on Soil Phosphorus in a Laboratory Incubation - Karen L. Grubb; Joshua M. McGrath; Chad J. Penn; Ray B. Bryant (Applied and Environmental Soil Science)
Agricultural drainage ditches can deliver high loads of phosphorus (P) to surface water. Installation of filter structures containing P sorbing materials (PSMs), including gypsum, is an emerging practice that has shown promise to reduce these P loads. The objective of this study was to evaluate what effect soil amendment with gypsum would have on soil P concentrations and forms in a laboratory incubation experiment. Gypsum was saturated at two levels with P, and applied to a silt loam and a sandy loam at two rates. The treated soils were incubated in the laboratory at 25°C, and samples were collected on eight dates between 0 and 183 days after amendment. Spent gypsum application did not significantly increase soil water-extractable or Mehlich 3 P when applied at typical agronomic rates. This appears to be a viable strategy to remove P from agricultural drainage waters but does not appear to provide any additional P fertilizer value.